PHYSICAL EDUCATION AND HEALTH INITIATIVES FOR HANDICAPPED YOUNG PEOPLE - Popova, N.V.; Joftsidu, D A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze benefits of adaptive physical education and sport service for the hearing-impaired young people. Methods and structure of the study. The two-stage survey was run at the Sverdlovsk and Kamensk-Uralsky Hearing-Impaired Service Offices of the All-Russian Hearing-impaired People’s Society in the Sverdlovsk Oblast. Stage 1 (2020) included a questionnaire survey of the 18-35 year-old (n=32) hearing-impaired youth to analyze their self-fulfillment needs, options and opportunities. The sample was surveyed on the opportunities for their initiatives in youth organizations, at places of residence and education establishments, and their adaptation and socialization problems and potential solutions. Results and conclusion. The survey found a range of problems in the practical opportunities for the hearing-impaired youth initiatives. Most of the sample reported disbeliefs in the real opportunities to implement their leisure-time and physical education-and-sport / health-related ideas and initiatives via the formal youth organizations. This is the reason for us to recommend special efforts to facilitate joint activities of hearing-impaired youth with their healthy peers.